Impact of Merdeka Curriculum Implementation on Student Character Development in Sekolah Penggerak Donggala Regency - Muliati Mursak; Arita Marini; Linda Zakiah (Universitas Sebelas Maret, 2024)
The development of student character is an essential element in education that must be consistently nurtured to promote positive growth. A well-designed curriculum plays a pivotal role in achieving this objective. This study investigates the impact of the Merdeka Curriculum on students' character development. The research used a quantitative approach with a survey design focused on five driving schools in Donggala Regency, Central Sulawesi. Data collection methods included in-depth interviews and comprehensive documentation studies. The collected data were analyzed using descriptive techniques to provide a thorough understanding of trends and outcomes. The findings highlight that SDN 25 Banawa achieved the highest overall scores, while SDN 16 Banawa recorded the lowest average score among the schools studied. Despite this variation, a general upward trend in character development was observed across all schools over the past three years. The results indicate that the implementation of the Merdeka Curriculum has a measurable positive effect on student character development. Nevertheless, active involvement from parents is deemed crucial to enhance further and maximize this developmental process. Therefore, fostering strong collaboration between schools and families is strongly recommended to optimize the potential of the Merdeka Curriculum in shaping the character of students in a comprehensive and sustainable manner